1965
DOI: 10.1037/h0021718
|View full text |Cite
|
Sign up to set email alerts
|

The experimenter effect.

Abstract: Recent investigations in experimental psychology have shown somewhat striking results which indicate that experimenters (Es) may and do influence their data. This problem was considered in relation to the areas of: experimental, counseling, and testing psychology. A historical review revealed that although the influence of E has been generally acknowledged, an unconcerned attitude towards this phenomenon has been taken, especially by experimental psychologists. Counseling psychology has been most concerned wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Calculation errors made by a scientist tend to favor the scientist's hypothesis (see [14], [25]). The reactions of the subjects may be affected by the experimenter's bias (see [15], [25]). Sometimes the bias is so strong that it leads to cheating, as is the well-known cases of Isaac Newton in the physical sciences [33], Cyril Burt in psychology [27], and William Summerlin in biology [8], [9].…”
Section: Empirical Evidence On Advocacy and Its Alternativesmentioning
confidence: 99%
“…Calculation errors made by a scientist tend to favor the scientist's hypothesis (see [14], [25]). The reactions of the subjects may be affected by the experimenter's bias (see [15], [25]). Sometimes the bias is so strong that it leads to cheating, as is the well-known cases of Isaac Newton in the physical sciences [33], Cyril Burt in psychology [27], and William Summerlin in biology [8], [9].…”
Section: Empirical Evidence On Advocacy and Its Alternativesmentioning
confidence: 99%
“…Scores on attitude tests often show a bias toward the more socially acceptable position because test takers, whether to conceal their prejudices or in denial of them (Lalwani, Shavitt, & Johnson, 2006;Nederhof, 1985), soften their responses such that prejudice that exists in actuality goes unmeasured. The tradition of explaining the effect of experimenter characteristics in terms of social desirability by asserting that participants purposely alter their test results in response to their perceptions of the experimenter has a long history (Kállai, Barke, & Voss, 2004;Kintz, Delprato, Mettee, Persons, & Schappe, 1965;Nederhof, 1985;Riemer & Shavitt, 2011;Silverman, 1974). For example, Kállai et al (2004) found an increase in participants' self-reported pain tolerance when tested by an experimenter of the opposite sex, and interpreted this as evidence that participants intentionally misrepresented their pain tolerance to impress the experimenter.…”
Section: Psi Chi Journal Of Psychological Researchmentioning
confidence: 99%
“…Firstly there are those which deal with situational and experimental factors which affect dream content and are thought to be germane to the laboratory. The experimenter can be seen to interact with treatment on the basis of such factors as: personality, experience and sex gender (Kintz et al, 1965). Moreover the experimenter is susceptible to bias in that he may contaminate data by the expectancies he entertains as to the outcome of the experiment (Rosenthal, 1965) or by information accrued in early data returns (Rosenthal, et al, 1963).…”
Section: Rem Dreams and 'Home' Dreamsmentioning
confidence: 99%
“…Moreover the experimenter is susceptible to bias in that he may contaminate data by the expectancies he entertains as to the outcome of the experiment (Rosenthal, 1965) or by information accrued in early data returns (Rosenthal, et al, 1963). As Kintz et al (1965) (Rosenthal, 1966).…”
Section: Rem Dreams and 'Home' Dreamsmentioning
confidence: 99%